Catalysts for electrochemical oxygen reduction
By using the combination of platinum nanoparticles with melamine compounds or thiol melamine compounds in the electrode catalyst, the durability and oxygen reduction activity of the electrode under high acidity conditions are improved, and the problem of insufficient durability in the prior art is solved, and the problem of reducing the System cost.
Patent Information
- Application Number
- CN202080075825.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-08
- Filing Date
- 2020-10-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-10-28
AI Technical Summary
In the prior art, the electrode catalyst has insufficient durability under high acidity conditions, especially at 70-85°C, resulting in low oxygen reduction reaction activity and large overvoltage, which increases system cost.
Compositions containing platinum nanoparticles and specific melamine compounds or thiol melamine compounds are used as electrochemical oxygen reduction catalysts to enhance the durability and oxygen reduction activity of the catalyst by supporting these compounds.
High oxygen reduction activity and durability at 70-85°C are achieved, overvoltage is reduced, platinum is used, and system cost is reduced.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst for electrochemical oxygen reduction. Background Art
[0002] From the viewpoints of being compact and highly efficient as well as global environmental issues, polymer electrolyte fuel cells (PEFC) are expected to become widespread in the near future.
[0003] Usually, the polymer electrolyte used for PEFC is a highly acidic cation exchange membrane, so the electrode catalyst needs to stably play a role under highly acidic conditions. For this reason, at present, the electrode catalyst that can be actually used is only platinum or an alloy containing platinum. Therefore, the price and scarcity of platinum become one of the main reasons for increasing the cost of the entire system. In particular, the oxygen reduction reaction of the air electrode is slow, so the overvoltage is large, and a large amount of platinum is used in order to obtain a sufficient reaction speed, therefore, it also becomes the main reason for increasing the cost of the entire system. In addition, the low durability of the platinum catalyst of the air electrode also becomes the reason why the amount of platinum used cannot be reduced. In order to reduce the cost of the entire system, it is strongly necessary to reduce the amount of precious metals used in the air electrode.
[0004] As methods for reducing such a large overvoltage, a method of alloying platinum and a method of using core-shell nanoparticles containing platinum are also known (for example, see Patent Document 1). In addition, a method of reducing overvoltage by modifying a porphyrazine compound on the surface of platinum is also known (for example, see Patent Document 2). Moreover, a method of reducing overvoltage by modifying a melamine compound on the surface of platinum is also known (for example, see Non-Patent Document 1).
[0005] However, metal-air batteries are batteries that use metals represented by zinc, iron, aluminum, etc. for the negative electrode and air electrodes for the positive electrode. These batteries can use oxygen in the air as the active material on the positive electrode side, and the capacitance is determined only by the negative electrode capacity, so high energy density can be achieved. In the metal-air battery, it is also known that the reaction on the air electrode (cathode) side is an oxygen reduction reaction during discharge and an oxygen generation reaction during charging. Therefore, in metal-air batteries, like PEFC, an air electrode with oxygen as an active material is used, so it is necessary to develop a catalyst that is highly active with respect to the oxygen reduction reaction.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-092940
[0009] Patent Document 2: Japanese Patent Application Publication No. 2018-086640
[0010] Non-patent literature
[0011] Non-patent document 1: 59th Battery Symposium Lecture No. 1H06 Summary of the invention
[0012] Technical problem to be solved by the invention
[0013] However, in the conventional methods such as Patent Documents 1 to 2 and Non-Patent Document 1, even if durability is achieved at room temperature, durability at 70 to 85°C, which is a practical temperature condition, cannot be said to be sufficient, and there is room for improvement in durability at 70 to 85°C, which is a practical temperature condition.
[0014] The present invention has been developed in view of the above-mentioned technical problems, and an object of the present invention is to provide a catalyst for electrochemical oxygen reduction which has high oxygen reduction activity (low overvoltage) and high durability at a practical temperature condition of 70 to 85°C.
[0015] Means for solving technical problems
[0016] The inventors of the present invention have repeatedly conducted in-depth research in view of the above technical problems. As a result, it was found that the above technical problems can be solved by including nanoparticles containing platinum and at least one selected from the group consisting of a polymer with a specific melamine compound as a monomer and a specific thiol melamine compound. The present invention was completed by further repeated research based on this understanding. That is, the present invention includes the following structure.
[0017] Item 1. A catalyst for electrochemical oxygen reduction, comprising:
[0018] Nanoparticles containing platinum, and
[0019] At least one selected from the group consisting of polymers containing melamine compounds as monomers and thiol melamine compounds, wherein:
[0020] The polymer having melamine compound as monomer is a polymer having repeating units represented by general formula (1),
[0021] [Chemical formula 1]
[0022]
[0023] [Where R 8 , R 9 , R 10 and R 11 are the same or different and represent a hydrogen atom, a hydroxyl group, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group. 12represents a substituted or unsubstituted alkylene group, a substituted or unsubstituted alkenylene group, a substituted or unsubstituted cycloalkylene group, or a substituted or unsubstituted arylene group. 8 , R 9 , R 10 and R 11 When neither is substituted by a sulfonic acid group or a derivative thereof (-SO3M; M represents a hydrogen atom, an alkali metal atom or NH4), R 12 represents a substituted or unsubstituted arylene group.]
[0024] The thiol melamine compound is a thiol melamine compound represented by the general formula (2).
[0025] [Chemical formula 2]
[0026]
[0027] [Where R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are the same or different and represent a hydrogen atom, a hydroxyl group, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group. 7 represents a substituted or unsubstituted alkylene group, a substituted or unsubstituted alkenylene group, a substituted or unsubstituted cycloalkylene group, or a substituted or unsubstituted arylene group.]
[0028] Item 2. The electrochemical oxygen reduction catalyst according to Item 1, wherein at least one selected from the group consisting of the polymer containing the melamine compound as a monomer and the thiol melamine compound is supported on the platinum-containing nanoparticles.
[0029] Item 3. The catalyst for electrochemical oxygen reduction according to Item 2, wherein:
[0030] 10 to 80% of the electrochemically active area (ECSA) of the platinum-containing nanoparticles, evaluated based on the amount of electricity caused by hydrogen desorption from the platinum surface, is covered with at least one selected from the group consisting of a polymer containing a melamine compound as a monomer and a thiol melamine compound.
[0031] Item 4. The catalyst for electrochemical oxygen reduction according to any one of Items 1 to 3, wherein
[0032] The polymer having a melamine compound as a monomer is a polymer having a repeating unit represented by the general formula (1A) or the general formula (1B).
[0033] [Chemical formula 3]
[0034]
[0035] [Where R 8 , R 9 , R 10 and R 11 are the same or different and represent a hydrogen atom, a hydroxyl group, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group. 12a represents a substituted or unsubstituted arylene group.]
[0036] [Chemical formula 4]
[0037]
[0038] [Where R 8a , R 9a , R 10a and R 11a are the same or different and represent a hydrogen atom, a hydroxyl group, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group. 8a , R 9a , R 10a and R 11a At least one of them is substituted by a sulfonic acid group or a derivative thereof (-SO3M; M represents a hydrogen atom, an alkali metal atom or NH4). 12 represents a substituted or unsubstituted alkylene group, a substituted or unsubstituted alkenylene group, a substituted or unsubstituted cycloalkylene group, or a substituted or unsubstituted arylene group.]
[0039] Item 5. The catalyst for electrochemical oxygen reduction according to Item 4, wherein
[0040] In the general formula (1A), R 8 , R 9 , R 10 and R 11 All are hydrogen atoms.
[0041] Item 6. The catalyst for electrochemical oxygen reduction according to Item 4 or 5, wherein
[0042] In the general formula (1B), R 8a , R 9a , R 10a and R 11a At least one of them is an alkyl group substituted with a sulfonic acid group or a derivative thereof (-SO3M; M represents a hydrogen atom, an alkali metal atom or NH4), and the others are hydrogen atoms.
[0043] Item 7. The catalyst for electrochemical oxygen reduction according to any one of Items 4 to 6, wherein
[0044] In the general formula (1B), R 12 is a substituted or unsubstituted alkylene group.
[0045] Item 8. The catalyst for electrochemical oxygen reduction according to any one of Items 1 to 7, wherein
[0046] In the general formula (2), R 1 , R 2 , R 3 , R 4 , R 5 and R 6 All are hydrogen atoms.
[0047] Item 9. The catalyst for electrochemical oxygen reduction according to any one of Items 1 to 8, wherein
[0048] In the general formula (2), R 7 is a substituted or unsubstituted alkylene group.
[0049] Item 10. The catalyst for electrochemical oxygen reduction according to any one of Items 1 to 9, which is supported on a conductive support.
[0050] Item 11. The catalyst for electrochemical oxygen reduction according to Item 10, wherein
[0051] The conductive carrier is a carbonaceous material.
[0052] Item 12. The catalyst for electrochemical oxygen reduction according to any one of Items 1 to 11, which is a cathode catalyst for a fuel cell.
[0053] Item 13. An air electrode for a fuel cell or a metal-air battery, using the catalyst for electrochemical oxygen reduction according to any one of Items 1 to 12.
[0054] Item 14. A fuel cell using the air electrode described in Item 13 as a positive electrode.
[0055] Item 15. A metal-air battery using the air electrode described in Item 13 as a positive electrode.
[0056] Effects of the Invention
[0057] According to the present invention, it is possible to provide an electrochemical oxygen reduction catalyst which has not only high oxygen reduction activity (small overvoltage) but also high durability at a practical temperature condition of 70 to 85°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a linear sweep voltammogram showing the results of Example 1 (durability test using melamine resin (1)).
[0059] Figure 2 This is a linear sweep voltammogram showing the results of Example 2 (durability test using melamine resin (2)).
[0060] Figure 3 This is a linear sweep voltammogram showing the results of Example 3 (durability test using a thiol melamine compound).
[0061] Figure 4 This is a linear sweep voltammogram showing the results of Comparative Example 1 (endurance test using an unsupported platinum catalyst).
[0062] Figure 5 This is a linear sweep voltammogram showing the results of Comparative Example 2 (durability test using melamine resin (3)). DETAILED DESCRIPTION
[0063] In this specification, "comprising" is a concept that includes all of "including", "consisting essentially of", and "consisting only of". In addition, in this specification, when a numerical range is described as A to B, it means greater than A and less than B.
[0064] 1. Catalysts for electrochemical oxygen reduction
[0065] The catalyst for electrochemical oxygen reduction of the present invention is a catalyst for electrochemical oxygen reduction, comprising nanoparticles containing platinum and at least one selected from the group consisting of a polymer with a melamine compound as a monomer and a thiol-melamine compound. In more detail, from the viewpoint of oxygen reduction activity or durability at 70 to 85°C as a practical temperature condition, it is preferred that at least one selected from the group consisting of a polymer with a melamine compound as a monomer and a thiol-melamine compound is loaded on nanoparticles containing platinum. That is, the nanoparticles containing platinum are preferably covered with their compounds. The catalyst for electrochemical oxygen reduction of the present invention may also contain the polymer with a melamine compound as a monomer and the thiol-melamine compound alone, or may contain two or more.
[0066] (1-1) Nanoparticles containing platinum
[0067] As the platinum-containing nanoparticles, catalysts currently used for air electrodes for fuel cells can be used, for example, platinum nanoparticles, platinum alloy nanoparticles, platinum-containing core-shell nanoparticles, and the like.
[0068] When platinum alloy nanoparticles are used, for example, an alloy of platinum and at least one of iron, nickel, manganese, copper, cobalt, chromium, titanium, ruthenium, rhodium, palladium, silver, iridium, gold, etc. is preferred. In this case, from the viewpoint of further reducing overvoltage, the content of platinum in the platinum alloy is preferably 50 to 95% by mass.
[0069] When core-shell nanoparticles containing platinum are used, it is preferred that the core contains a metal or its alloy cheaper than platinum and the shell contains platinum from the viewpoint of further reducing overvoltage and reducing the amount of platinum used. The platinum alloy of the core can be the above-mentioned platinum alloy.
[0070] The average particle size of the platinum-containing nanoparticles as described above is not particularly limited. When nanoparticles with a small average particle size are used, the active surface area increases, but too small platinum particles cannot stably exist at 70 to 85°C, which is a practical temperature condition. From this point of view, the average particle size of the platinum-containing nanoparticles is preferably 2nm to 40nm, more preferably 2.4nm to 30nm, and further preferably 3nm to 20nm. In the case of using core-shell nanoparticles containing platinum, the average thickness of the shell is preferably 1 to 3 atomic layers.
[0071] (1-2) Polymers using melamine compounds as monomers and thiol melamine compounds
[0072] [1-2-1] Polymers using melamine compounds as monomers
[0073] The polymer containing a melamine compound as a monomer is a polymer having a repeating unit represented by the general formula (1).
[0074] [Chemical formula 5]
[0075]
[0076] [Where R 8 , R 9 , R 10 and R 11 are the same or different and represent a hydrogen atom, a hydroxyl group, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group. 12 represents a substituted or unsubstituted alkylene group, a substituted or unsubstituted alkenylene group, a substituted or unsubstituted cycloalkylene group, or a substituted or unsubstituted arylene group. 8 , R 9 , R 10 and R 11 When neither is substituted by a sulfonic acid group or a derivative thereof (-SO3M; M represents a hydrogen atom, an alkali metal atom or NH4), R 12 represents a substituted or unsubstituted arylene group.]
[0077] When such a polymer containing a melamine compound as a monomer is used, durability at a practical temperature condition of 70 to 85° C. can be improved, and oxygen reduction activity can be improved (overvoltage can be reduced).
[0078] In the general formula (1), R 8 , R 9 , R 10 and R 11 Examples of the halogen atom represented by include a fluorine atom, a chlorine atom, a bromine atom, an iodine atom and the like.
[0079] In the general formula (1), R 8 , R 9 , R 10 and R 11 The alkyl group represented by may be, for example, a lower alkyl group (especially a straight-chain or branched alkyl group having 1 to 10 carbon atoms, and further 1 to 6 carbon atoms) such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, and n-hexyl. In addition, the alkyl group may also have, for example, 1 to 6 (especially 1 to 3) hydroxyl groups, the halogen atoms, amino groups, sulfonic acid or its derivative groups (-SO3M; M represents a hydrogen atom, an alkali metal atom or NH4.) and other substituents. In particular, when substituted with a sulfonic acid or its derivative group (-SO3M; M represents a hydrogen atom, an alkali metal atom or NH4.), the durability at 70 to 85°C, which is a practical temperature condition, can be further improved, and the oxygen reduction activity can be further improved (the overvoltage can be further reduced). It should be noted that in the sulfonic acid or its derivative group, as the alkali metal atom represented by M, lithium atom, sodium atom, potassium atom, cesium atom, etc. can be mentioned. As the sulfonic acid or its derivative group, a sulfonic acid group (—SO 3 H) is preferred from the viewpoints of oxygen reduction activity and durability at a practical temperature condition of 70 to 85° C.
[0080] In the general formula (1), R 8 , R 9 , R 10 and R 11 The alkenyl represented by may include, for example, vinyl, allyl, 2-butenyl, 3-butenyl, 1-methylallyl, 2-pentenyl, 2-hexenyl and other lower alkenyls (especially straight-chain or branched alkenyls having 2 to 10 carbon atoms, and further having 2 to 6 carbon atoms). In addition, the alkenyl group may also have, for example, 1 to 6 (especially 1 to 3) hydroxyl groups, the halogen atoms, amino groups, the sulfonic acid or its derivative groups and other substituents. In particular, when substituted with the sulfonic acid or its derivative groups, the durability at 70 to 85°C, which is a practical temperature condition, can be further improved, and the oxygen reduction activity can be further improved (further reducing the overvoltage).
[0081] In the general formula (1), R 8 , R 9 , R 10 and R 11 The aryl group represented by may include, for example, phenyl, naphthyl, anthracenyl and other aryl groups (especially aryl groups having 6 to 20 carbon atoms, and further 6 to 18 carbon atoms). In addition, the aryl group may also have, for example, 1 to 6 (especially 1 to 3) hydroxyl groups, the halogen atoms, the alkyl group, the alkenyl group, the amino group, the sulfonic acid or its derivative group and other substituents. In particular, when substituted with the sulfonic acid or its derivative group, the durability at 70 to 85°C, which is a practical temperature condition, can be further improved, and the oxygen reduction activity can be further improved (further reducing the overvoltage).
[0082] In the general formula (1), R 8 , R 9 , R 10 and R 11 From the viewpoint of further improving the durability at 70 to 85°C as a practical temperature condition and further improving the oxygen reduction activity (further reducing the overvoltage) and further reducing the amount of platinum used, it is preferably a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group, and more preferably a hydrogen atom, an alkyl group substituted by the sulfonic acid or its derivative group, an alkenyl group substituted by the sulfonic acid or its derivative group, an aryl group substituted by the sulfonic acid or its derivative group, and the like, and further preferably a hydrogen atom, an alkyl group substituted by the sulfonic acid or its derivative group, and the like. It should be noted that from the viewpoint of synthesis, it is particularly preferred to replace R 8 , R 9 , R 10 and R 11 are all assumed to be hydrogen atoms.
[0083] In the general formula (1), R 12 The alkylene group represented by , for example, includes lower alkylene groups (particularly linear or branched alkylene groups having 1 to 10 carbon atoms, and further 1 to 6 carbon atoms) such as methylene, ethylene, ethylidene, trimethylene, propylene, propane-2,2-diyl, tetramethylene, methyltrimethylene, ethylethylene, and dimethylethylene. The alkylene group may have, for example, 1 to 6 (particularly 1 to 3) hydroxyl groups, the above-mentioned halogen atoms, the above-mentioned alkenyl group, the above-mentioned aryl group, and an amino group as a substituent.
[0084] In the general formula (1), R 12Examples of the alkenylene group represented by include lower alkenylene groups (particularly straight-chain or branched alkenylene groups having 2 to 10 carbon atoms, and further having 2 to 6 carbon atoms) such as vinylene, vinylidene, 1-methylvinylene, propenylene, 1-butenylene, and 2-butenylene. The alkenylene group may have, for example, 1 to 6 (particularly 1 to 3) hydroxyl groups, the above-mentioned halogen atoms, the above-mentioned alkenyl group, the above-mentioned aryl group, and an amino group as a substituent.
[0085] In the general formula (1), R 12 Examples of the cycloalkylene group represented by include cycloalkylene groups (particularly cycloalkylene groups having 6 to 20 carbon atoms, and further 6 to 18 carbon atoms) such as cyclopropylene, cyclobutylene, cyclopentylene, cyclohexylene, decahydronaphthalene-2,6-diyl, and cyclohexene-1,2-diyl. The cycloalkylene group may have, for example, 1 to 6 (particularly 1 to 3) hydroxyl groups, the halogen atoms, the alkyl groups, the alkenyl groups, the aryl groups, and amino groups as substituents.
[0086] In the general formula (1), R 12 The arylene group represented by may include, for example, phenylene, naphthylene, anthracenediyl, phenanthrenediyl, biphenyldiyl, fluorenediyl and the like arylene groups (particularly arylene groups having 6 to 20 carbon atoms, and further 6 to 18 carbon atoms). The arylene group may have, for example, 1 to 6 (particularly 1 to 3) hydroxyl groups, the above halogen atoms, the above alkyl groups, the above alkenyl groups, the above aryl groups, amino groups and the like as substituents.
[0087] In the general formula (1), R 12 From the viewpoint of further improving the durability at 70 to 85° C., which is a practical temperature condition, and further improving the oxygen reduction activity (further reducing the overvoltage) to further reduce the amount of platinum used, a substituted or unsubstituted alkylene group is preferred.
[0088] In the present invention, in a polymer having a repeating unit represented by the general formula (1), by 8 , R 9 , R 10 and R 11 At least one of the sulfonic acid or its derivative group is introduced, or R 12 By making it a group that is not easily detached, the durability at 70 to 85°C, which is a practical temperature condition, can be improved, and the oxygen reduction activity can be improved (overvoltage can be reduced). 8 , R 9 , R 10 and R 11 When neither of them is substituted by the sulfonic acid or its derivative group, R 12 is a substituted or unsubstituted arylene group.
[0089] In other words, the polymer having a repeating unit represented by the general formula (1) as described above is preferably a polymer having a repeating unit represented by the general formula (1A) or the general formula (1B).
[0090] [Chemical formula 6]
[0091]
[0092] [Where R 8 , R 9 , R 10 and R 11 Same as above. 12a represents a substituted or unsubstituted arylene group.]
[0093] [Chemical formula 7]
[0094]
[0095] [Where R 8a , R 9a , R 10a and R 11a are the same or different and represent a hydrogen atom, a hydroxyl group, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group. 8a , R 9a , R 10a and R 11a At least one of them is substituted by a sulfonic acid group or a derivative thereof (-SO3M; M represents a hydrogen atom, an alkali metal atom or NH4). 12 Same as above.]
[0096] In the general formula (1A), R 12a The arylene group represented by may be the same as above, and the type and number of substituents are also the same. 8a , R 9a , R 10a and R 11a The halogen atoms, alkyl groups, alkenyl groups and aryl groups represented by may be the same as those described above, and the types and numbers of substituents are also the same. 8a , R 9a , R 10a and R 11a In particular, from the viewpoint of further reducing the amount of platinum used by improving the durability at a practical temperature condition such as 70 to 85°C and improving the oxygen reduction activity (reducing the overvoltage), R 8a , R 9a , R 10a and R 11aAt least one of them is an alkyl group substituted by the sulfonic acid or its derivative group, and the others are hydrogen atoms, and more preferably R 8a , R 9a , R 10a and R 11a One of them is an alkyl group substituted by the sulfonic acid or its derivative group, and the others are hydrogen atoms. 8a , R 9a , R 10a and R 11a When the sulfonic acid or its derivative group is substituted, the number of the sulfonic acid or its derivative group is not particularly limited, and can be, for example, 1 to 3.
[0097] It should be noted that when a polymer having a repeating unit represented by the general formula (1A) is used as a polymer having a melamine compound as a monomer, the durability at 70 to 85°C, which is a practical temperature condition, can be improved, and the oxygen reduction activity can be improved (reduced overvoltage), but when a polymer having a repeating unit represented by the general formula (1B) is used as a polymer having a melamine compound as a monomer, it is possible to improve the durability at 70 to 85°C, which is a practical temperature condition, and the oxygen reduction activity can be improved (reduced overvoltage).
[0098] Examples of the repeating unit satisfying the above conditions include the following:
[0099] [Chemical formula 8]
[0100]
[0101] wait.
[0102] Such a polymer containing a melamine compound as a monomer may be a polymer consisting only of repeating units represented by the general formula (1) or may be a melamine resin represented by the general formula (3).
[0103] [Chemical formula 9]
[0104]
[0105] [Where R 8 , R 9 , R 10 , R 11 and R 12 Same as above. n represents an integer from 2 to 1000.]
[0106] A typical example of such a polymer is a sulfonated melamine condensate (melamine sulfonic acid) represented by the following general formula (3A).
[0107] [Chemical formula 10]
[0108]
[0109] [Where R 8 , R 9 , R 11 and n are the same as above.]
[0110] The degree of polymerization of the polymer having a melamine compound as a monomer (corresponding to n in the case of the melamine resin represented by the general formula (3)) is not particularly limited, but from the viewpoint of further improving the durability at 70 to 85°C, which is a practical temperature condition, and further improving the redox activity (further reducing the overvoltage) to further reduce the amount of platinum used, the average (representative) degree of polymerization is preferably 2 to 1000, and more preferably 3 to 500.
[0111] It should be noted that the terminal group of the polymer having the melamine compound as a monomer is not particularly limited, and can generally be a hydrogen atom, a hydroxyl group, the above-mentioned alkyl group, the above-mentioned alkenyl group, the above-mentioned aryl group, or the like.
[0112] As the polymer having a melamine compound as a monomer and satisfying the above-mentioned conditions, a known product or a commercially available product can be used.
[0113] [1-2-2]Melamine Thiol Compounds
[0114] The thiol melamine compound is a thiol melamine compound represented by the general formula (2).
[0115] [Chemical formula 11]
[0116]
[0117] [Where R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are the same or different and represent a hydrogen atom, a hydroxyl group, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group. 7 represents a substituted or unsubstituted alkylene group, a substituted or unsubstituted alkenylene group, a substituted or unsubstituted cycloalkylene group, or a substituted or unsubstituted arylene group.]
[0118] When such a thiol melamine compound is used, durability at a practical temperature condition of 70 to 85° C. can be improved, and oxygen reduction activity can be improved (overvoltage can be reduced).
[0119] In the general formula (2), R 1 , R 2 , R 3 , R4 , R 5 and R 6 The halogen atoms, alkyl groups, alkenyl groups and aryl groups represented may be the same as those described above, and the types and numbers of substituents are also the same.
[0120] In the general formula (2), R 1 , R 2 , R 3 , R 4 , R 5 and R 6 From the viewpoint of further improving the durability at practical temperature conditions such as 70 to 85°C and further improving the oxygen reduction activity (further reducing the overvoltage) to further reduce the amount of platinum used, preferably a hydrogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, or a substituted or unsubstituted aryl group, more preferably a hydrogen atom, an alkyl group substituted by the sulfonic acid or its derivative group, an alkenyl group substituted by the sulfonic acid or its derivative group, an aryl group substituted by the sulfonic acid or its derivative group, etc., further preferably a hydrogen atom, an alkyl group substituted by the sulfonic acid or its derivative group, etc. It should be noted that from the viewpoint of synthesis, it is particularly preferred to replace R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are all assumed to be hydrogen atoms. In addition, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 It can be the same or different.
[0121] In the general formula (2), R 7 The alkylene group, alkenylene group, cycloalkylene group and arylene group represented may be the same as those described above, and the types and numbers of substituents are also the same.
[0122] In the general formula (2), R 7 From the viewpoint of further improving the durability at about 70 to 85° C., which is a practical temperature condition, and further improving the oxygen reduction activity (further reducing the overvoltage) to further reduce the amount of platinum used, a substituted or unsubstituted alkylene group is preferred.
[0123] Examples of the thiol melamine compound satisfying the above conditions include the following compounds:
[0124] [Chemical formula 12]
[0125]
[0126] As such a mercaptan melamine compound, a known compound may be used, or it may be synthesized separately.
[0127] In the catalyst for electrochemical oxygen reduction of the present invention, the amount of the polymer with melamine compound as monomer and the thiol melamine compound is not particularly limited. For example, it is preferred to contain (especially to load) 0.1 to 1000 parts by mass, especially 0.5 to 800 parts by mass relative to 100 parts by mass of nanoparticles containing platinum, and at least one selected from the group consisting of polymers with melamine compound as monomer and thiol melamine compound. In addition, it is preferred that 10 to 80%, especially 20 to 70%, of the electrochemical active area (ECSA) of the nanoparticles containing platinum, which is evaluated based on the amount of electricity caused by hydrogen desorption on the surface of platinum, is covered by at least one selected from the group consisting of polymers with melamine compound as monomer and thiol melamine compound. That is, the coating rate of the nanoparticles containing platinum coated with these compounds is preferably 10 to 80%, and particularly preferably 20 to 70%. In addition, when using a polymer which uses a melamine compound as a monomer and a thiol melamine compound in plurality, it is preferable to adjust the total amount thereof to the above range.
[0128] (1-3) Conductive carrier
[0129] The described nanoparticles containing platinum can further improve electrical conductivity and can reduce the amount of platinum used by being supported on a conductive carrier. As a conductive carrier, as long as it can be used for a conductive carrier of a catalyst currently used for electrochemical reduction of oxygen, there is no particular restriction, for example, conductive oxides such as carbonaceous materials such as carbon black (ketjen black, furnace black, acetylene black, etc.), activated carbon, graphite, glassy carbon, tin or titanium can be enumerated. Among these materials, from the viewpoint of conductivity and surface area, preferred carbon black.
[0130] The shape of the conductive support is not particularly limited, but is preferably a shape that conforms to the shape of the air electrode.
[0131] (1-4) Catalysts for electrochemical oxygen reduction
[0132] The shape of the catalyst for electrochemical oxygen reduction of the present invention is not particularly limited, and may be a shape that conforms to the shape of the air electrode.
[0133] The electrochemical oxygen reduction catalyst of the present invention has oxygen reduction activity for reducing oxygen to water, and therefore can be suitably used as an electrode catalyst for a battery using oxygen as an active material. Specifically, it can be suitably used as an air electrode catalyst for a fuel cell (particularly a solid polymer fuel cell, a phosphoric acid fuel cell, etc.) or a metal-air battery.
[0134] 2. Method for producing electrochemical oxygen reduction catalyst
[0135] The method for producing the electrochemical redox catalyst of the present invention is not particularly limited. For example, at least one selected from the group consisting of the polymer with the melamine compound as a monomer and the thiol melamine compound can be loaded on the platinum-containing nanoparticles by a dissolution drying method, a coating method, a gas phase method, etc.
[0136] For example, in the dissolution drying method, nanoparticles containing platinum (especially platinum catalyst) and at least one selected from the group consisting of a polymer with melamine compound as a monomer and a thiol melamine compound are pre-dissolved or dispersed (suspended) in a solvent, and stirred as needed, thereby, nanoparticles containing platinum (especially platinum catalyst) are adsorbed at least one selected from the group consisting of a polymer with melamine compound as a monomer and a thiol melamine compound, and then the obtained suspension is filtered as needed and the powder is recovered, thereby, the electrochemical oxygen reduction catalyst of the present invention can be obtained. In addition, in the coating method, nanoparticles containing platinum (especially platinum catalyst) can be used to form on an electrode, and then, a solution containing at least one selected from the group consisting of a polymer with melamine compound as a monomer and a thiol melamine compound is applied. It should be noted that, in the case where nanoparticles containing platinum are supported on a conductive carrier, loading can be performed by a common method. In addition, in the catalyst in which nanoparticles containing platinum are supported on a conductive carrier, a polymer having a melamine compound as a monomer and a thiol melamine compound may be supported by the same method as described above.
[0137] As the solvent, any solvent can be used without particular limitation as long as it can dissolve or disperse (suspend) the nanoparticles containing platinum and the polymer and the thiol melamine compound with the melamine compound as the monomer. For example, organic solvents or water such as acetone, toluene, methanol, ethanol, 1-propanol, 2-propanol, methylene chloride, tetrahydrofuran, acetonitrile, dimethylformamide, etc. can be used appropriately. These organic solvents and water can also be used alone or in combination of two or more.
[0138] The concentration of at least one of the platinum-containing nanoparticles (particularly platinum catalysts) and the group consisting of a polymer with a melamine compound as a monomer and a thiol melamine compound is not particularly limited, and can be adjusted to the above-mentioned usage amount. For example, as the addition amount, the concentration of the platinum-containing nanoparticles (particularly platinum catalysts) is preferably 0.1 to 10.0 g / L, and more preferably 0.5 to 5.0 g / L. In addition, as the addition amount, the concentration of the polymer with a melamine compound as a monomer and the thiol melamine compound in the solvent is preferably 0.02 to 3.0 g / L, and more preferably 0.05 to 1.5 g / L.
[0139] 3. Air electrode and battery
[0140] The air electrode of the present invention is an air electrode for a fuel cell (particularly for a polymer electrolyte fuel cell, a phosphoric acid fuel cell, etc.) or a metal-air battery using the electrochemical oxygen reduction catalyst of the present invention.
[0141] Such an air electrode can be the same as a conventional air electrode except that the catalyst for electrochemical oxygen reduction of the present invention is used as a catalyst. For example, the air electrode of the present invention may include an air electrode catalyst layer.
[0142] The thickness of the air electrode catalyst layer is not particularly limited, and can generally be set to about 0.1 to 100 μm. In addition, the amount of catalyst is also not particularly limited, and can be, for example, 0.01 to 20 mg / cm 2 about.
[0143] The method for forming the air electrode catalyst layer is not particularly limited, and the air electrode catalyst layer can be formed by applying a catalyst ink prepared by mixing the electrochemical oxygen reduction catalyst of the present invention with a resin solution onto a gas diffusion layer, a current collector, etc., and drying the mixture.
[0144] The structure of other air electrodes may be the same as that of known air electrodes. For example, the structure may be as follows: a current collecting material such as carbon paper, carbon cloth, metal mesh, metal sintered body, foamed metal plate, or metal porous body is arranged on the catalyst layer side of the air electrode, and a waterproof membrane, diffusion membrane, air distribution layer, etc. are arranged.
[0145] As an electrolyte, the electrochemical oxygen reduction catalyst of the present invention and the polymer electrolyte membrane can be integrated and used by a known method. A catalyst layer can also be formed on the electrolyte membrane by applying a material obtained by dispersing the electrochemical oxygen reduction catalyst of the present invention and electrolyte materials, carbon materials, etc. using water or a solvent, or by transferring the catalyst layer applied to the substrate to the electrolyte membrane.
[0146] As the polymer electrolyte membrane, various ion exchange resin membranes represented by perfluorocarbon-based, styrene-divinylbenzene copolymer-based, and polybenzimidazole-based ion exchange resin membranes, inorganic polymer ion exchange membranes, organic-inorganic composite polymer ion exchange membranes, and the like can be used.
[0147] The structure of the fuel electrode is not particularly limited either, and can be set to be the same as the structure of a known solid polymer fuel cell. As the catalyst for the fuel electrode, various metals, metal alloys, metal complexes known at present can also be used. As usable metal species, in addition to the precious metals such as platinum, palladium, iridium, rhodium, ruthenium, gold used in existing solid polymer fuel cells (PEFC), base metals such as nickel, silver, cobalt, iron, copper, zinc, etc. can also be cited. A single metal catalyst or metal complex selected from these metals, an alloy or a complex of a metal complex composed of any combination of two or more metals can be used. In addition, it can also be used as a composite catalyst, a catalyst particle dispersed in a carbonaceous material, a supported catalyst on a carrier such as a metal oxide selected from the above.
[0148] A polymer electrolyte fuel cell can also be produced by sandwiching both sides of the obtained membrane-electrode assembly with current collectors such as carbon paper and carbon cloth and incorporating the assembly into a battery.
[0149] On the other hand, when the invention is applied to a phosphoric acid fuel cell instead of a solid polymer fuel cell, the polymer electrolyte membrane may not be used, but phosphoric acid aqueous solution may be impregnated into various separators as an electrolyte. The other components are the same as those of the solid polymer fuel cell.
[0150] In addition, when the catalyst for electrochemical oxygen reduction of the present invention is used for the air electrode of a metal-air battery, a metal such as zinc, aluminum, magnesium, or iron can be used as the metal negative electrode in the metal-air battery. The specific structure of the metal negative electrode can be the same as that of a known metal-air battery. The other components are the same as those of a solid polymer fuel cell.
[0151] In the battery of the above structure, oxygen or air can be supplied to the air electrode side or diffused naturally in any case. In addition, in a fuel cell (particularly a solid polymer fuel cell, a phosphoric acid fuel cell, etc.), a substance that becomes a fuel can be supplied to the fuel electrode side. As a fuel substance, in addition to hydrogen, alcohols such as methanol, ethanol, isopropanol, ethylene glycol, formic acid, borohydride salts, hydrazine, sugar solutions, etc. can be used.
[0152] It should be noted that when the battery of the present invention is a fuel cell (particularly a polymer electrolyte fuel cell, a phosphoric acid fuel cell, etc.), the operating temperature varies depending on the electrolyte used, but is generally about 0 to 250°C, preferably about 10 to 80°C.
[0153] Example
[0154] The present invention will be described in more detail below with reference to Examples and Comparative Examples. It should be noted that the present invention is not limited to the following Examples. In addition, the following compounds were used as polymers using melamine compounds as monomers and thiol melamine compounds.
[0155] [Chemical formula 13]
[0156] Melamine resin (1) Synthesis Example 1:
[0157]
[0158] Melamine resin (2): Axcelead 100 (sulfonated melamine condensate) manufactured by Nissan Chemical Industries, Ltd.
[0159] [Chemical formula 14]
[0160] Melamine resin (3): poly(melamine-co-oxymethylene) methyl ester solution manufactured by Sigma-Aldrich Co., Ltd. (R: hydrogen atom or methyl group)
[0161]
[0162] [Chemical formula 15]
[0163] Thiol melamine compound (Synthesis Example 2):
[0164]
[0165] Synthesis Example 1: Melamine resin (1)
[0166] The melamine resin (1) is synthesized by the following method. 1-Methyl-2-pyrrolidone as a reaction solvent is added to 1,3-phenylenediamine, and the mixture is stirred while nitrogen substitution is performed to dissolve the mixture. Then, 2-amino-4,6-dichloro-1,3,5-triazine is added and stirred to dissolve the mixture. Then, potassium carbonate is added and stirred for 15 minutes to disperse the mixture. After stirring in an oil bath at 150°C for 85 hours, the mixture is cooled to room temperature and added dropwise to purified water (3000 mL) containing aqueous ammonia (28%, 30 mL), and stirred for 30 minutes. After filtering out the precipitate and washing it three times with purified water (150 mL), methanol (450 mL) is added and stirred for 90 minutes. After removing the methanol by filtering out, the mixture is washed three times with methanol (150 mL). Next, the mixture is dried under reduced pressure (60°C) under heating to obtain a brown solid (yield 54.4%).
[0167] [Chemical formula 16]
[0168] 1,3-phenylenediamine
[0169]
[0170] [Chemical formula 17]
[0171] 2-Amino-4,6-dichloro-1,3,5-triazine
[0172]
[0173] Synthesis Example 2: Thiol melamine compound
[0174] The raw material 1 (2-chloro-4,6-diamino-1,3,5-triazine; 1.45 g, 10 mmol (manufactured by Tokyo Chemical Industry Co., Ltd.)) and the raw material 2 (2-aminoethanethiol; 771 mg, 10 mmol (manufactured by Tokyo Chemical Industry Co., Ltd.)) were suspended and dissolved in 25 mL of water in an argon-substituted reactor, and stirred and refluxed for 3 hours. The transparent solution was filtered, and 2 mL of water containing 0.4 g of sodium hydroxide was added, followed by stirring and reflux for 1 hour. Then, the reaction solution was returned to room temperature, and the filtered solid was thoroughly washed with water and further vacuum dried to obtain the target thiol melamine compound. When ASAP-MS (atmospheric pressure solid sample analysis probe mass spectrometry) was measured, the peak of m / z187, which is the ion of the product molecule +H, was observed, confirming the synthesis of the target. In addition, a different amino group from that of raw material 1 was observed at 5.9 to 6.7 ppm. 1 HNMR peak, and the synthesis of the target product was confirmed.
[0175] [Chemical formula 18]
[0176] Raw material 1 (2-chloro-4,6-diamino-1,3,5-triazine)
[0177]
[0178] [Chemical formula 19]
[0179] Raw material 2 (2-aminoethanethiol)
[0180]
[0181] Example 1: Durability test using melamine resin (1)
[0182] 5 mg of a platinum catalyst (TEC10E50E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.; average particle size 2-3 nm) was suspended in a mixed solvent of 5.14 mL of ultrapure water and 1.62 mL of 2-propanol, and 3.6 μL of the suspension was dropped onto a glassy carbon electrode (area: 0.0707 cm) with a diameter of 3 mm manufactured by BAS Co., Ltd. 2 ) and let it dry.
[0183] The catalyst modified electrode was set as the working electrode, the reversible hydrogen electrode was set as the reference electrode, and the platinum coil was set as the counter electrode, and electrochemical measurement was performed by three electrodes. A 0.1M perchloric acid aqueous solution was used as the electrolyte. First, after the cyclic voltammetry measurement was performed under an argon atmosphere, the gas atmosphere was changed to oxygen, and the linear sweep voltammogram was measured from the low potential side. Thus, the oxygen reduction activity when a catalyst containing neither melamine resin nor thiol melamine compound was used was evaluated.
[0184] Next, the electrode was taken out and immersed in a pyridine solution (0.7 mmol / L) of melamine resin (1) for 10 minutes to allow the melamine resin (1) to adsorb on the platinum catalyst, and then the same measurement as before the immersion was performed again. Thus, the oxygen reduction activity of the catalyst loaded with melamine resin (1) on platinum can be evaluated. At this time, the coverage of the platinum catalyst by melamine resin (1) calculated according to ECSA was 65%.
[0185] Then, 3.6 μL of Nafion solution (a solution obtained by adding 27 μL of Nafion (Aldrich 5 wt%) to a mixed solvent of 5.14 mL of water + 1.62 mL of 2-propanol) was added dropwise to the catalyst-modified electrode loaded with melamine resin (1) and dried at room temperature, and the electrode was set as the working electrode, the reversible hydrogen electrode was set as the reference electrode, the platinum coil was set as the counter electrode, and the electrolyte was set as a 0.1 M aqueous perchloric acid solution. A durability test was performed by a three-electrode method at 77°C, in which a rectangular wave potential cycle was applied for 10,000 cycles, with the working electrode being maintained at 0.6 V for three seconds and at 1.0 V for three seconds. Then, the same measurement as before immersion was performed. Thus, the oxygen reduction activity after the durability test when a catalyst containing melamine resin (1) was used can be evaluated.
[0186] The mass activity per 1 g of platinum was used as an activity index. The mass activity value was calculated by the following formula.
[0187] Mass activity = [1 / (amount of platinum on the electrode (g))] × (current value at 0.9 V)(current value at 0.38 V) / [(current value at 0.38 V)-(current value at 0.9 V)]
[0188] In the above calculation formula, the current value at 0.38 V represents the upper limit of the current value limited by mass migration, and the mass activity value is a value reflecting only the catalyst activity in which the effect of mass migration is eliminated.
[0189] The result is Figure 1 As shown in Figure 1 As shown, in terms of mass activity at a potential of 0.9 V vs RHE, before impregnation (before melamine resin (1) loading) is 410 AgPt -1 , after impregnation (after melamine resin (1) loading) is 371Ag Pt -1 , but after the durability test it becomes 450Ag Pt -1 After the durability test, the mass activity at a potential of 0.9 V vs RHE was maintained at about 110%, and degradation was suppressed through the durability test, while maintaining a state of high redox activity and low overvoltage.
[0190] Example 2: Durability test using melamine resin (2)
[0191] 5 mg of a platinum catalyst (TEC10E50E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.; average particle size 2-3 nm) was suspended in a mixed solvent of 5.14 mL of ultrapure water and 1.62 mL of 2-propanol, and 3.6 μL of the suspension was dropped onto a glassy carbon electrode (area: 0.0707 cm) with a diameter of 3 mm manufactured by BAS Co., Ltd. 2 ) and let it dry.
[0192] The catalyst modified electrode was set as the working electrode, the reversible hydrogen electrode was set as the reference electrode, and the platinum coil was set as the counter electrode, and electrochemical measurement was performed by three electrodes. A 0.1M perchloric acid aqueous solution was used as the electrolyte. First, after the cyclic voltammetry measurement was performed under an argon atmosphere, the gas atmosphere was changed to oxygen, and the linear sweep voltammogram was measured from the low potential side. Thus, the oxygen reduction activity when a catalyst containing neither melamine resin nor thiol melamine compound was used was evaluated.
[0193] Next, 0.027 mL of a solution prepared by diluting melamine resin (2) 5 times with pure water was added dropwise to a mixed solvent of 5.14 mL of ultrapure water and 1.62 mL of 2-propanol. Then, the electrode used for the evaluation was taken out, and 3.6 μL of the solution of melamine resin (2) prepared as described above was applied to the electrode (area: 0.0707 cm 2 ) and dried, and the same measurement as before coating was performed again using the obtained electrode. Thus, the oxygen reduction activity of the catalyst loaded with melamine resin (2) on platinum can be evaluated. At this time, the coverage of the platinum catalyst by melamine resin (2) calculated according to ECSA was 47%.
[0194] Then, 3.6 μL of Nafion solution (a solution obtained by adding 27 μL of Nafion (Aldrich 5wt%) to a mixed solvent of 5.14 mL of water + 1.62 mL of 2-propanol) was added to the catalyst-modified electrode loaded with melamine resin (2) and dried at room temperature, and the electrode was set as the working electrode, the reversible hydrogen electrode was set as the reference electrode, the platinum coil was set as the counter electrode, and the electrolyte was set as a 0.1 M aqueous perchloric acid solution. A durability test was performed by a three-electrode method at 77°C, in which a rectangular wave potential cycle was applied for 10,000 cycles, with the working electrode maintained at 0.6 V for three seconds and at 1.0 V for three seconds. Then, the same measurement as before immersion was performed. Thus, the oxygen reduction activity after the durability test when using a catalyst containing melamine resin (2) can be evaluated. It should be noted that as an indicator of activity, the mass activity per 1 g of platinum was used as in Example 1.
[0195] The result is Figure 2 As shown in Figure 2 , in terms of mass activity at a potential of 0.9 V vs RHE, before impregnation (before melamine resin (2) loading) is 409 Ag Pt -1 , after impregnation (after melamine resin (2) loading) is 501Ag Pt -1 , but after the durability test it became 397Ag Pt -1 After the durability test, the mass activity at a potential of 0.9 V vs RHE can be maintained at about 97%, and degradation can be suppressed through the durability test, maintaining a state of high redox activity and low overvoltage.
[0196] Example 3: Durability test using mercaptan melamine compounds
[0197] 5 mg of a platinum catalyst (TEC10E50E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.; average particle size 2-3 nm) was suspended in a mixed solvent of 5.14 mL of ultrapure water and 1.62 mL of 2-propanol, and 3.6 μL of the suspension was dropped onto a glassy carbon electrode (area: 0.0707 cm) with a diameter of 3 mm manufactured by BAS Co., Ltd. 2 ) and let it dry.
[0198] The catalyst modified electrode was set as the working electrode, the reversible hydrogen electrode was set as the reference electrode, and the platinum coil was set as the counter electrode, and electrochemical measurement was performed by three electrodes. A 0.1M perchloric acid aqueous solution was used as the electrolyte. First, after the cyclic voltammetry measurement was performed under an argon atmosphere, the gas atmosphere was changed to oxygen, and the linear sweep voltammogram was measured from the low potential side. Thus, the oxygen reduction activity when a catalyst containing neither melamine resin nor thiol melamine compound was used was evaluated.
[0199] Next, the electrode was taken out and immersed in an acetone solution (0.7 mmol / L) of a thiol melamine compound for 10 minutes to allow the thiol melamine compound to adsorb to the platinum catalyst, and then the same measurement as before the immersion was performed again. Thus, the oxygen reduction activity of the catalyst loaded with the thiol melamine compound on the platinum can be evaluated. At this time, the coverage of the platinum catalyst by the thiol melamine compound calculated according to ECSA was 47%.
[0200] In addition, 3.6 μL of Nafion solution (a solution obtained by adding 27 μL of Nafion (Aldrich 5wt%) to a mixed solvent of 5.14 mL of water + 1.62 mL of 2-propanol) was added to the catalyst-modified electrode loaded with the thiol melamine compound and dried at room temperature as the working electrode, the reversible hydrogen electrode as the reference electrode, the platinum coil as the counter electrode, and the electrolyte as a 0.1 M aqueous perchloric acid solution. A three-electrode method was used to perform a durability test at 77°C by applying a rectangular wave potential cycle of 2800 cycles at 0.6 V for three seconds and 1.0 V for three seconds. Then, the same measurement as before immersion was performed. Thus, the oxygen reduction activity after the durability test when using a catalyst containing a thiol melamine compound can be evaluated. It should be noted that as an indicator of activity, the mass activity per 1 g of platinum is used as in Example 1.
[0201] The result is Figure 3 As shown in Figure 3 , in terms of mass activity at a potential of 0.9 V vs RHE, before impregnation (before loading of the thiol melamine compound) is 330 Ag Pt -1 , after impregnation (after loading of thiol melamine compound) is 468Ag Pt -1 , but after the durability test it becomes 401Ag Pt -1 After the durability test, the mass activity at a potential of 0.9 V vs RHE can be maintained at about 120%, and degradation can be suppressed through the durability test, maintaining a state of high redox activity and low overvoltage.
[0202] Comparative Example 1: Durability test using unsupported platinum catalyst
[0203] 5 mg of a platinum catalyst (TEC10E50E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.; average particle size 2-3 nm) was suspended in a mixed solvent of 5.14 mL of ultrapure water and 1.62 mL of 2-propanol, and 3.6 μL of the suspension was dropped onto a glassy carbon electrode (area: 0.0707 cm) with a diameter of 3 mm manufactured by BAS Co., Ltd. 2 ) and let it dry.
[0204] The catalyst modified electrode was set as the working electrode, the reversible hydrogen electrode was set as the reference electrode, and the platinum coil was set as the counter electrode, and electrochemical determination was performed by a three-electrode method. The electrolyte used a 0.1M perchloric acid aqueous solution. First, after the determination of cyclic voltammetry under an argon atmosphere, the gas atmosphere was changed to oxygen, and the determination of a linear sweep voltammogram was performed from the low potential side. At this time, the electrode was rotated at 1600 rpm. Thus, the oxygen reduction activity when a catalyst containing neither melamine resin nor any of the mercaptan melamine compounds was used was evaluated.
[0205] Next, 3.6 μL of Nafion solution (a solution obtained by adding 27 μL of Nafion (Aldrich 5wt%) to a mixed solvent of 5.14 mL of water + 1.62 mL of 2-propanol) was added to the catalyst modified electrode and dried at room temperature, and the electrode was set as the working electrode, the reversible hydrogen electrode was set as the reference electrode, the platinum coil was set as the counter electrode, and the electrolyte was set as a 0.1M perchloric acid aqueous solution. A three-electrode method was used to perform a durability test in which a rectangular wave potential cycle was applied at 77°C for 2800 cycles or 10000 cycles, with the working electrode maintained at 0.6 V for three seconds and at 1.0 V for three seconds. Then, as described above, after the cyclic voltammetry measurement was performed under an argon atmosphere, the gas atmosphere was changed to oxygen, and the linear sweep voltammogram was measured from the low potential side. Thus, the oxygen reduction activity after the durability test when a catalyst containing neither the melamine resin nor the thiol-melamine compound was used was evaluated. In addition, as an activity index, similarly to Example 1, the mass activity per 1 g of platinum was used.
[0206] The result is Figure 4 As shown in Figure 4 As shown in the figure, the mass activity per 1g of platinum calculated from the current at a potential of 0.9 V vs RHE was 468 Ag before the endurance test in the endurance test of 2800 cycles. Pt -1 , but after the durability test it becomes 225Ag Pt -1 , in the endurance test of 10000 cycles, the value before the endurance test was 532Ag Pt -1 , but after the durability test it became 257Ag Pt -1 In any case, after the endurance test, the mass activity at a potential of 0.9 V vs RHE was about 48%, and the redox activity was lowered and the overvoltage was increased due to the degradation caused by the endurance test.
[0207] Comparative Example 2: Durability test using melamine resin (3)
[0208] 5 mg of a platinum catalyst (TEC10E50E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.; average particle size 2-3 nm) was suspended in a mixed solvent of 5.14 mL of ultrapure water and 1.62 mL of 2-propanol, and 3.6 μL of the suspension was dropped onto a glassy carbon electrode (surface area: 0.0707 cm) manufactured by BAS Co., Ltd. 2 ) and let it dry.
[0209] The catalyst modified electrode was set as the working electrode, the reversible hydrogen electrode was set as the reference electrode, and the platinum coil was set as the counter electrode, and electrochemical measurement was performed by three electrodes. A 0.1M perchloric acid aqueous solution was used as the electrolyte. First, after the cyclic voltammetry measurement was performed under an argon atmosphere, the gas atmosphere was changed to oxygen, and the linear sweep voltammogram was measured from the low potential side. Thus, the oxygen reduction activity when a catalyst containing neither melamine resin nor thiol melamine compound was used was evaluated.
[0210] Next, 0.027 mL of a 5% butanol solution of melamine resin (3) was added to a mixed solvent of 5.14 mL of ultrapure water and 1.62 mL of 2-propanol. Then, the electrode was taken out, and 3.6 μL of the diluted melamine resin (3) solution prepared in this way was added dropwise to the taken-out electrode, and the same measurement as before immersion was performed again. Thus, the oxygen reduction activity of the catalyst loaded with melamine resin (3) on platinum can be evaluated. At this time, the coverage of the platinum catalyst coated with melamine resin (3) calculated according to ECSA was 47%.
[0211] Furthermore, 3.6 μL of Nafion solution (a solution obtained by adding 27 μL of Nafion (Aldrich 5 wt%) to a mixed solvent of 5.14 mL of water + 1.62 mL of 2-propanol) was added dropwise to a catalyst-modified electrode loaded with melamine resin (3) and dried at room temperature, and a working electrode was set, a reversible hydrogen electrode was set as a reference electrode, a platinum coil was set as a counter electrode, and an electrolyte was set as a 0.1 M aqueous perchloric acid solution. A three-electrode method was used to perform a durability test at 77°C, in which a rectangular wave potential cycle was applied for 2800 cycles and 10000 cycles, with the working electrode maintained at 0.6 V for three seconds and at 1.0 V for three seconds. Then, the same measurement as before immersion was performed. Thus, the oxygen reduction activity after the durability test when a catalyst containing melamine resin (3) was used can be evaluated. It should be noted that as an indicator of activity, the mass activity per 1 g of platinum was used as in Example 1.
[0212] The result is Figure 5 As shown in Figure 5 In terms of mass activity at a potential of 0.9 V vs RHE, in a durability test of 2800 cycles, before impregnation (before loading with melamine resin (3)) was 440 AgPt -1 , after impregnation (after melamine resin (3) loading) is 739Ag Pt -1 , but after the durability test it became 239Ag Pt -1 In the durability test of 10,000 cycles, the value before impregnation (before loading with melamine resin (3)) was 541Ag Pt -1 , after impregnation (after melamine resin (3) loading) is 1036Ag Pt -1 , but after the durability test it becomes 176Ag Pt -1 After the endurance test, the mass activities at a potential of 0.9 V vs RHE were about 54% and about 32%, respectively. Due to the deterioration caused by the endurance test, the redox activity became lower and the overvoltage became larger.
[0213] Industrial Applicability
[0214] The catalyst for electrochemical oxygen reduction of the present invention can be used, for example, in an air electrode (cathode) of a fuel cell, a metal-air battery, or the like.
Claims
1. A catalyst for electrochemical oxygen reduction, comprising: Nanoparticles containing platinum, and At least one selected from the group consisting of polymers containing melamine compounds as monomers and thiol melamine compounds, The polymer having melamine compound as monomer is a polymer having repeating units represented by general formula (1), ; In formula (1), R 8 , R 9 , R 10 and R 11 are the same or different and represent a hydrogen atom, a linear or branched alkyl group having 1 to 10 carbon atoms, or a linear or branched alkyl group having 1 to 10 carbon atoms substituted with 1 to 6 hydroxyl groups, or a sulfonic acid or a derivative thereof, wherein: The sulfonic acid or its derivative group is represented by -SO3M, wherein M represents a hydrogen atom, an alkali metal atom or NH4; R 12 represents a linear or branched alkylene group having 1 to 10 carbon atoms, or an arylene group having 6 to 18 carbon atoms; wherein R 8 , R 9 , R 10 and R 11 When neither of them is substituted by the sulfonic acid or its derivative group, R 12 represents an arylene group having 6 to 18 carbon atoms, The thiol melamine compound is a thiol melamine compound represented by the general formula (2), ; In formula (2), R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are the same or different and represent a hydrogen atom or a linear or branched alkyl group having 1 to 10 carbon atoms; R 7 represents a linear or branched alkylene group having 1 to 10 carbon atoms, or an arylene group having 6 to 18 carbon atoms; The average polymerization degree of the polymer containing the melamine compound as a monomer is 2 to 1000.
2. The catalyst for electrochemical oxygen reduction according to claim 1, wherein At least one selected from the group consisting of the polymer containing a melamine compound as a monomer and the thiol melamine compound is supported on the platinum-containing nanoparticles.
3. The catalyst for electrochemical oxygen reduction according to claim 2, wherein: 10 to 80% of the electrochemically active area ECSA of the platinum-containing nanoparticles evaluated by the amount of electricity caused by hydrogen desorption from the platinum surface is covered with at least one selected from the group consisting of a polymer containing a melamine compound as a monomer and a thiol melamine compound.
4. The catalyst for electrochemical oxygen reduction according to any one of claims 1 to 3, wherein The polymer having a melamine compound as a monomer is a polymer having a repeating unit represented by the general formula (1A) or the general formula (1B), ; In formula (1A), R 8 , R 9 , R 10 and R 11 are the same or different and represent a hydrogen atom or a linear or branched alkyl group having 1 to 10 carbon atoms; R 12a represents an arylene group having 6 to 18 carbon atoms, ; In formula (1B), R 8a , R 9a , R 10a and R 11a are the same or different and represent a hydrogen atom, a straight-chain or branched alkyl group having 1 to 10 carbon atoms, or a straight-chain or branched alkyl group having 1 to 10 carbon atoms substituted with 1 to 6 hydroxyl groups, or a sulfonic acid or its derivative group, wherein the sulfonic acid or its derivative group is represented by -SO3M, wherein M represents a hydrogen atom, an alkali metal atom or NH4; wherein R 8a , R 9a , R 10a and R 11a At least one of R is substituted by the sulfonic acid or its derivative group; 12 It represents a linear or branched alkylene group having 1 to 10 carbon atoms, or an arylene group having 6 to 18 carbon atoms.
5. The catalyst for electrochemical oxygen reduction according to claim 4, wherein In the general formula (1A), R 8 , R 9 , R 10 and R 11 All are hydrogen atoms.
6. The catalyst for electrochemical oxygen reduction according to claim 4, wherein In the general formula (1B), R 8a , R 9a , R 10a and R 11a At least one of them is an alkyl group substituted by a sulfonic acid or a derivative thereof, wherein the sulfonic acid or a derivative thereof is represented by -SO3M, wherein M represents a hydrogen atom, an alkali metal atom or NH4; and the others are hydrogen atoms.
7. The catalyst for electrochemical oxygen reduction according to claim 4, wherein In the general formula (1B), R 12 is a substituted or unsubstituted alkylene group.
8. The catalyst for electrochemical oxygen reduction according to any one of claims 1 to 3, wherein In the general formula (2), R 1 , R 2 , R 3 , R 4 , R 5 and R 6 All are hydrogen atoms.
9. The catalyst for electrochemical oxygen reduction according to any one of claims 1 to 3, wherein In the general formula (2), R 7 is a substituted or unsubstituted alkylene group.
10. The catalyst for electrochemical oxygen reduction according to any one of claims 1 to 3, wherein The electrochemical oxygen reduction catalyst is supported on a conductive carrier.
11. The catalyst for electrochemical oxygen reduction according to claim 10, wherein The conductive carrier is a carbonaceous material.
12. The catalyst for electrochemical oxygen reduction according to any one of claims 1 to 3, wherein The electrochemical oxygen reduction catalyst is a cathode catalyst for a fuel cell. 13 . An air electrode for a fuel cell or a metal-air battery, comprising the catalyst for electrochemical oxygen reduction according to claim 1 .
14. A fuel cell using the air electrode according to claim 13 as a positive electrode. 15 . A metal-air battery using the air electrode according to claim 13 as a positive electrode.
